Understanding the role of scientific knowledge transfer in the women’s participation and farmer activities in Central Java - Dharmawan, Budi; Krott, Max; Prasetyo, Kunandar (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
The forest turns to agricultural land in the Serayu watershed in Central Java, Indonesia. The Strengthening Community-Based Forest and Watershed Management (SCBFWM) project aims to improve and expand the Indonesian government’s community-based forest and watershed management programs. The study’s objectives are: 1) investigate the factors that contribute to the successful implementation of scientific findings in everyday life; 2) analyze the potential impacts of alternative strategies for the development of farming systems in the watershed on rural livelihoods; and 3) analyze the rules and governance structure that organizes the action of actors and how decisions are made. We use the RIU (Research-IntegrationUtilization) Model to examine how scientific research can yield effective policy advice and decision-maker’s role in transforming advice into effective problem-solving. The findings that emerged from the research demonstrated that the district government cares about the environment but does not prohibit upstream potato cultivation strictly. When the SCBFWM project was established, cultivation restrictions were implemented. The research on the importance of women’s participation in watershed management was communicated to the district administration and included in the SCBFWM project’s proposal, but the actual action was different. The RIU model demonstrated that high-quality science is insufficient without efficient integration and acknowledges the inherent divergent interests within science and policy